SPATIAL-TEMPORAL DYNAMICS LAND USE/LAND COVER CHANGE AND FLOOD HAZARD MAPPING IN THE UPSTREAM CITARUM WATERSHED, WEST JAVA, INDONESIA - Yulianto, Fajar; Suwarsono, Suwarsono; Nugroho, Udhi Catur; Nugroho, Nunung Puji; Sunarmodo, Wismu; Khomarudin, Muhammad Rokhis (Quaestiones Geographicae, 2020)
This study presents the information on the dynamics of changes in land use/land cover (LULC) spatially and temporally related to the causes of flooding in the study area. The dynamics of LULC changes have been derived based on the classification of Landsat imagery for the period between 1990 and 2016. Terrain surface classification (TSC) was proposed as a micro-landform classification approach in this study to create flood hazard assessment and mapping that was produced based on the integration of TSC with a probability map for flood inundation, and flood depth information derived from field observation. TSC as the micro-landform classification approach was derived from SRTM30 DEM data. Multi-temporal Sentinel-1 data were used to construct a pattern of historical inundation or past flooding in the study area and also to produce the flood probability map. The results of the study indicate that the proposed flood hazard mapping (FHM) from the TSC as a micro-landform classification approach has the same pattern with the results of the integration of historical inundation or previous floods, as well as field investigations in the study area. This research will remain an important benchmark for planners, policymakers and researchers regarding spatial planning in the study area. In addition, the results can provide important input for sustainable land use plans and strategies for mitigating flood hazards.